AN INTEGRATIVE FRAMEWORK BETWEEN TDABC AND THE BALANCED SCORECARD: THE ROLE OF ADVANCED STATISTICAL MODELING IN IMPROVING INSTITUTIONAL PERFORMANCE IN THE HEALTHCARE SECTOR - Abbas Hamed Abbas; Aqeel Saad Jabar; Ali Awadh Atshan (Journal of Economic and Economic Policy, 2026)
Objective: This study proposes an integrative model that combines Time-Driven Activity-Based Costing (TDABC) and the Balanced Scorecard (BSC) to strengthen financial decision-making and organizational performance in healthcare institutions. Method: A mixed-methods research approach was applied, incorporating qualitative case studies and quantitative techniques, including regression analysis and Monte Carlo simulations, to evaluate the impact of the TDABC-BSC integration. Results: The findings demonstrate a 20% reduction in patient service costs, a 27.7% improvement in financial sustainability, and a 23.6% increase in resource utilization efficiency. However, implementation resistance (40%) and data availability constraints (25%) highlight the need for strategic planning, standardized reporting, and AI-driven predictive analytics. Novelty: This research provides the first empirical framework demonstrating the effectiveness of integrating TDABC with BSC for achieving financial sustainability and strategic performance alignment in healthcare organizations, offering actionable insights for administrators, policymakers, and researchers.